2021
DOI: 10.1152/ajpendo.00393.2020
|View full text |Cite
|
Sign up to set email alerts
|

Increased vascular permeability and severe renal tubular damage after ischemia-reperfusion injury in mice lacking adiponectin or T-cadherin

Abstract: In the kidney, T-cadherin-associated adiponectin protein existed on peritubular capillary pericytes. In an acute renal ischemia-reperfusion model, deficiency of adiponectin or T-cadherin exhibited the more progressive phenotype of renal tubular damage and increased vascular permeability, accompanied by severe pericyte loss. In vitro, adiponectin promoted exosome secretion from mouse primary pericytes in a T-cadherin-dependent manner. Adiponectin plays an important role in maintaining the capillary network and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 54 publications
5
21
0
2
Order By: Relevance
“…3E and 3G). Under non-diabetic conditions, no alteration of retinal vasopermeability was observed in APN-KO mice, which is consistent with previous results demonstrating that APN de ciency did not in uence physiological characteristics, including insulin resistance (1), cardiac function (2), and renal vascular permeability (11). On the contrary, APN-KO mice exhibited severely increased vascular permeability under a relatively short term of hyperglycemia, despite similar blood glucose levels to diabetic WT mice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3E and 3G). Under non-diabetic conditions, no alteration of retinal vasopermeability was observed in APN-KO mice, which is consistent with previous results demonstrating that APN de ciency did not in uence physiological characteristics, including insulin resistance (1), cardiac function (2), and renal vascular permeability (11). On the contrary, APN-KO mice exhibited severely increased vascular permeability under a relatively short term of hyperglycemia, despite similar blood glucose levels to diabetic WT mice.…”
Section: Discussionsupporting
confidence: 91%
“…APN circulates abundantly in human bloodstream (1 to 30 μg/mL), but its concentration decreases under pathological conditions, such as obesity, especially visceral fat accumulation (6), and type 2 diabetes (7). We and others previously reported that APN protein, but not gene expression, exists in the aortic endothelium, heart, skeletal muscle, proliferative smooth muscle cells, and renal pericytes through binding to T-cadherin, a unique glycosylphosphatidylinositol (GPI)-anchored cadherin (8)(9)(10)(11). Moreover, APN exhibited its protective effects on atherosclerosis (8), cardiac hypertrophy (9), muscle regeneration (10), and renal tubular injury (11) in a T-cadherin-dependent manner.…”
mentioning
confidence: 99%
“…Recent studies, including our own, have shown T-cadherin-dependent APN accumulation in various types of tissues and cells [8][9][10][11]21,22 . The present study clearly demonstrated that APN was predominantly localized in the vascular endothelium of retinal arterioles.…”
Section: Discussionmentioning
confidence: 75%
“…This result suggests a gradual decline of endothelial T-cadherin expression associated with the transition from arterioles to capillaries, which is compatible with recent single cell RNA-sequencing data from brain endothelial cells (BECs) 23 . We recently reported that, in kidney, both APN and T-cadherin were observed in platelet-derived growth factor receptor beta (PDGFRβ)-positive pericytes of peritubular capillaries, but not in glomerular or peritubular capillary endothelium 11 . However, in retina, no APN signal was found in NG2-positive pericytes in the capillary layer (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation